Root cause analysis of an unexpected brittle failure in a carbon steel slab. (April 2021) - Keramatian, Ali; Bahrami, Abbas; Darougheh, Amir Hossein; Zare, Shahin
Highlights: Failure of a steel slab in a steel production plant is investigated. Microstructural characteristics is comprehensively investigated. The correlations between the microstructure and observed failure are discussed. The failure is related to high nitrogen content of the alloy. Abstract: This paper investigates the root cause of an unexpected brittle transverse cracking in a carbon steel slab. The observed failure in the form of a deep and relatively straight transverse crack appeared in the middle of the slab during storage before hot rolling. The microstructure of the failed slab, and more specifically that in the vicinity of the crack were studied using electron and optical microscopy. Energy-dispersive X-ray spectroscopy (EDS) was used to study the chemical composition of different phases, observed in the microstructure. Analysis of the chemical composition of the alloy showed that chromium and nitrogen contents of the failed slab were out of standard range. Results of fractography showed that grain boundary de-cohesion and trans-granular fracture were dominant features in the fracture surface. Correlations between microstructure, processing parameters, and observed abnormal brittle fracture were discussed.